2011
DOI: 10.1002/adma.201102331
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Carbon Nanotube Array as Dry Adhesive for High‐Temperature Silicon Processing

Abstract: CNT arrays are used as removable dry adhesives for high‐temperature processes with temperatures that increase by as much as 900 °C. The adhesion force between the self‐assembled CNTs is utilized to strain the microstructures in high‐temperature environments. Arrays of analog micromirrors are successfully fabricated by silicon processing. The proposed method significantly simplifies the fabrication process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…As a result, CNT forests can be produced on silicon and other high-temperature substrates, 8,9 non-horizontal surfaces, 4 and can be coated or infiltrated with other materials to form microstructured composites. 10,11 The three-dimensional geometry of CNT forests has also been exploited as a structural support for high aspect ratio micro structures, 11 a damping layer, 12 a high temperature dry adhesive material, 13 and was integrated into MEMS devices vertical comb-drive. 14 Moreover, CNT forests playing an instrumental role as an electrical component in several applications, for example, robust electrodes, 4 micro capacitors, 15 vertical comb-drive fingers, 14 and electrostatically actuated CNT varactors, 16 were reported.…”
mentioning
confidence: 99%
“…As a result, CNT forests can be produced on silicon and other high-temperature substrates, 8,9 non-horizontal surfaces, 4 and can be coated or infiltrated with other materials to form microstructured composites. 10,11 The three-dimensional geometry of CNT forests has also been exploited as a structural support for high aspect ratio micro structures, 11 a damping layer, 12 a high temperature dry adhesive material, 13 and was integrated into MEMS devices vertical comb-drive. 14 Moreover, CNT forests playing an instrumental role as an electrical component in several applications, for example, robust electrodes, 4 micro capacitors, 15 vertical comb-drive fingers, 14 and electrostatically actuated CNT varactors, 16 were reported.…”
mentioning
confidence: 99%
“…However, the usual quantum mechanical Raman theory [150] presents some flaws [229] in agreement with the point that the quantum mechanical theory generally neglects the locality of energy states and that the law of energy conservation is not always respected [26,98]. We state that the description of the double resonance back scattering on defects and edges and which is supposed to give account for the so-called “Ddisorder” peak (at ~1350 cm −1 ) does not fulfill the energy conservation law [26] (only the momentum conservation).…”
Section: Brief Review Of Revisited Carbon Raman Spectroscopymentioning
confidence: 91%
“…The NEMS technology is distinguished from molecular nanotechnology or molecular electronics in that the latter must also consider surface chemistry and solid-state phonon and electronic quantum mechanical aspects which can affect mechanical, electric and optoelectronic properties, friction and that can cause high signal/noise ratio ([89,90,91,92]. Mechanical deformation and electrical contact properties and adhesion between carbon nanotubes are important aspects of their quality and dynamic performances [93,94,95,96,97,98] and explaining why they must be selected and controlled upon their characteristics, size and defect content.…”
Section: Brief Review On Main Mems and Nems Characteristicsmentioning
confidence: 99%
“…For example, CNTs, 1D carbon atom structures with diameters in the nanometer range, have many advantages for use in moving parts of M/NEM switches, such as superior mechanical strength, electrical conductivity, and thermal conductivity 20,21,32,244–248. Moreover, recent advanced CNT fabrication processes have enabled implementation of CNTs in 3D structures 249–251. Indeed, many studies have been reported of low‐voltage operating M/NEM switching devices that exploit CNTs for structural material 211,213,215,252–256.…”
Section: High‐performance Nems/mems Devicesmentioning
confidence: 99%